Immunomodulatory and therapeutic implications of vitamin D in the management of COVID-19 - Manish Dhawan; Priyanka; Om Prakash Choudhary (Taylor & Francis Group, 2022)
COVID-19 has caused severe financial, clinical, and sociological consequences besides posing a burden on healthcare. Many nutritional approaches have been employed to manage the deleterious consequences of COVID-19. Among the several micronutrients, vitamin D deprivation has been linked to an increased likelihood of hospitalization of COVID-19 patients. Vitamin D has been reported to be a critical regulator of the renin-angiotensin system, which is used by the SARS-CoV-2 to access the host cell. Vitamin D also modulates the multiple immune system mechanisms to contain the virus, including the curtailment of the viral entry into the host cell. The adequate levels of vitamin D in the host have been associated with the reduced release of proinflammatory cytokines, thus lowering the risk of a cytokine storm; increased levels of anti-inflammatory cytokines and enhanced secretion of natural antimicrobial peptides. It may also be involved in the enhancement of the Th2 immune response and activation of defensive cells such as macrophages. Contrary to these findings, several studies have concluded that there is no direct association between vitamin D concentrations and poor prognosis of the disease. Hence, this paper aims to decipher the immunoregulatory properties of vitamin D and its possible involvement in management of COVID-19.